Chemical investigation of the non-alkaloidal constituents of the leaves and stem bark of Kibatalia gitingensis (Elm.) woods. (Fam. Apocynaceae) - Rivera, Thelma A.
The air dried leaves and stem bark of Kibatalia gitingensis (Elm.) Woods. yielded 0.18% and 0.41% respectively, on the dry basis, of identical mixtures of triterpenoids. The major triterpenoid was identified as α-amyrin acetate, m.p. 224-226(degrees C) and the minor triterpenoid as α-amyrin, m.p. 180-185(degrees C). These triterpenoid isolates were analyzed by TLC, color reactions, and spectroscopic methods. Further confirmation on their identifications was done by comparison with reference samples.